The potential of task shifting selected maternal interventions to auxiliary midwives in Myanmar: a mixed-method study - Kyu Kyu Than; Khaing Nwe Tin; Thazin La; Kyaw Soe Thant; Theingi Myint; James G. Beeson; Stanley Luchters; Alison Morgan (BMC, 2018)
Abstract Background An estimated 282 women die for every 100,000 live births in Myanmar, most due to preventable causes. Auxiliary Midwives (AMWs) in Myanmar are responsible for providing a package of care during pregnancy and childbirth to women in rural hard to reach areas where skilled birth attendants (Midwives) are not accessible. This study aims to examine the role of AMWs in Myanmar and to assess the current practices of three proposed essential maternal interventions (oral supplement distribution to pregnant women; administration of misoprostol to prevent postpartum haemorrhage; management of puerperal sepsis with oral antibiotics) in order to facilitate a formal integration of these tasks to AMWs in Myanmar. Methods A mixed methods study was conducted in Magwe Region, Myanmar involving a survey of 262 AMWs, complemented by 15 focus group discussions with midwives (MWs), AMWs, mothers and community members, and 10 key informant interviews with health care providers at different levels within the health care system. Results According to current government policy, AMWs are responsible for identifying pregnant women, screening for danger signs and facilitating early referral, provision of counselling on nutrition and birth preparedness for women in hard-to-reach areas. AMWs also assist at normal deliveries and help MWs provide immunization services. In practice, they also provide oral supplements to pregnant women (84%), provide antibiotics to mothers during the puerperium (43%), and provide misoprostol to prevent postpartum haemorrhage (41%). The current practices of AMWs demonstrate the potential for task shifting on selected essential maternal interventions. However, to integrate these interventions into formal practice they must be complemented with appropriate training, clear guidelines on drug use, systematic recording and reporting, supportive monitoring and supervision and a clear political commitment towards task shifting. Conclusion With the current national government's commitment towards one AMW in one village, this study highlights the potential for shifting specific maternal lifesaving tasks to AMWs.